Simulation design for thermal model from various materials in electronic devices: A review - Bahru R.; Zamri M.F.M.A.; Shamsuddin A.H.; Mohamed M.A. (Taylor and Francis Ltd., 2023)
Electronic equipment; Heat transfer performance; Thermography (temperature measurement); Device design; Electronics devices; Heat transfer performance; Property; Simulation Design; Simulation studies; Simulation;; Thermal management;; Thermal materials; Thermal model; Thermoelectric equipment